Comprehensive analysis of the mechanical system system “fixture – workpiece” - V. Ivanov; I. Pavlenko (Журнал інженерних наук)
Present work is devoted to locating and clamping of prismatic parts in fixtures during the machining on drilling-milling-boring machines. The special feature of locating schemes of parts of the present type is that one of the flat surfaces is used as a datum (3 contact points) ensuring stability, convenience of locating and vibration elimination during the machining process. Within the scope of the presented work, the comprehensive mathematical model of the system “fixture – workpiece” has been developed taking into account technological features of locating and clamping processes of workpiece in fixture. The methodology of determination of the rigidity of the cutting tool and functional elements has been proposed. As a result, the static and dynamic analysis of the workpiece in the fixture under the effect of spatial system of cutting and clamping forces is being determined. In addition, the free frequencies of the system “fixture-workpiece” and forms of the free and forced vibrations, frequency-response characteristics are being determined. Keywords: locating chart, functional element, rigidity, free vibrations, free frequency, forced vibrations, cutting force, frequency-response characteristic